STRATEGIES FOR CURRICULUM IMPLEMENTATION IN NIGERIAN TEACHER EDUCATION: A FOCUS ON KNOWLEDGE MANAGEMENT - Afolabi, Oluwatobi Kehinde (Ayden Journal of Management and Social Sciences, 2024)
The study investigated curriculum implementation and knowledge management in Nigerian teacher education process. The objective was to determine the extent of knowledge management in teacher education process in Nigeria. Two research questions were answered and one hypothesis tested. The study adopted descriptive survey design with a population of 226 lecturers in the Faculty of Education, Prince Abubakar Audu University, Anyigba, Kogi State and Rivers State University, Port Harcourt. A sample size of 80 lecturers was drawn using the proportionate stratified random sampling technique. The instrument for data collection was an 18- item questionnaire validated by three experts and it gave a reliability coefficient of 0.72 which was obtained using Cronbach Alpha method. The data collected was analyzed with mean and standard deviation and z-test for the hypothesis. The findings showed adequate management support for lecturers in North Central and inadequate management support for lecturers in the South-South and it was also revealed that there was poor provision of resources as perceived by male and female lecturers in teacher education process in Nigeria. It was then concluded that more work was required to boost management support for curriculum implementation in teacher education process, especially, in the South-South Nigeria.